1992
DOI: 10.2135/cropsci1992.0011183x003200030034x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Metabolism of Normal and High‐Seed‐Protein Soybean

Abstract: Nitrogen metabolism differences, including N2 fixation, between high‐and normal‐seed‐protein soybean [Glycine max (L.) Merr.] lines of equivalent plant maturity and seed yielding ability have not been determined in field tests. A replicated field experiment was conducted in 1985 and 1986 to determine such differences on a Mattapex silt loam (fine, silty, mixed, mesic Aqualfic Hapludult) with low soil N. The study used the nodulating‐nonnodulating N difference method to estimate N2 fixation of two soybean lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 0 publications
3
22
0
2
Order By: Relevance
“…We also found genotypic variation in these traits related to N redistribution, but none of the variation was related to seed N concentration or total seed N at maturity in the six genotypes in our experiment. Consistent with our findings, Leffel et al (1992) found no increase in remobilization efficiency [(maximum vegetative N -vegetative N at R8)/maximum vegetative N] in a single high seed protein genotype. There was no relationship between the contribution of redistributed N and yield in commercial cultivars from maturity groups II to V (Zeiher et al 1982), II (Vasilas et al 1995) or 00 and 0 (Kumudini et al 2002).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found genotypic variation in these traits related to N redistribution, but none of the variation was related to seed N concentration or total seed N at maturity in the six genotypes in our experiment. Consistent with our findings, Leffel et al (1992) found no increase in remobilization efficiency [(maximum vegetative N -vegetative N at R8)/maximum vegetative N] in a single high seed protein genotype. There was no relationship between the contribution of redistributed N and yield in commercial cultivars from maturity groups II to V (Zeiher et al 1982), II (Vasilas et al 1995) or 00 and 0 (Kumudini et al 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Leffel et al (1992) found that N fixation of a single high-protein genotype was higher than the normal protein control during seed filling. Vasilas et al (1995) and Kumudini et al (2002) found the high yield was associated with greater N acquisition during seed filling, instead of a larger supply from redistribution.…”
Section: Discussionmentioning
confidence: 92%
“…In soybean, the occurrence of cultivar x Bradyrhizobium strain interactions was established for the percent N derived from the atmosphere (Rennie & Dubetz, 1984) or for the amount of fixed N2 (Ravuri & Hume, 1993) in field trials. However, such effects were not detected by other authors (Leffel et al, 1992), sometimes even in spite of refined experimental designs (Buttery & Dirks, 1987). The importance ofcultivar x strain interactions remains unpredictable as they depend on the combinations studied.…”
Section: Discussionmentioning
confidence: 86%
“…The extra cost of N2 fixation could be assumed by most field-grown legume crops without any major loss of productivity since factors other than energy supply for N2 fixation were generally involved in legume growth limitation (Herridge & Bergersen, 1988). Improving N2 fixation then should not penalize productivity and could even facilitate the elaboration of high seed protein contents in soybean (Leffel et al, 1992). Indeed, rapid N2 fixation during pod filling was shown to contribute to increased seed yield and seed protein content (Imsande, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variation among soybean cultivars exists in all aspects of the signaling pathway; some genotypes are better able to select strains with greater symbiotic efficiency or maintain nitrogen fixation later in the growing season (Leffel et al 1992;de O. Chueire and Hungria 1997;Rengel 2002;Salvagiotti et al 2008;Messmer et al 2011). Mycorrhizal fungi are less host-specific than rhizobia, but the extent and benefit of colonization nonetheless depend on host genotype (Rengel 2002;Messmer et al 2011).…”
Section: Modification Of the Soil Bacterial Communitymentioning
confidence: 99%